2009
DOI: 10.1007/978-3-642-03658-3_11
|View full text |Cite
|
Sign up to set email alerts
|

Bodily Explorations in Space: Social Experience of a Multimodal Art Installation

Abstract: Abstract.We contribute with an extensive field study of a public interactive art installation that applies multimodal interface technologies. The installation is part of a Theater production on Galileo Galilei and includes: projected galaxies that are generated and move according to motion of visitors changing colour depending on their voices; projected stars that configure themselves around shadows of visitors. In the study we employ emotion scales (PANAS), qualitative analysis of questionnaire answers and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Several approaches have been presented for evaluating such criteria both qualitatively and qualitatively. Jaccucci et al [15] mention several quantitative methods and end up using Positive and Negative Affect Schedule (PANAS) [16] together with interviews and video recordings to evaluate visitor experiences of two interactive art installations. Similarly, Kortbek & Grønbaek [17] use a mixed methods approach including their own multiple-choice questionnaire and interviews to evaluate interactive installations in an art museum.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been presented for evaluating such criteria both qualitatively and qualitatively. Jaccucci et al [15] mention several quantitative methods and end up using Positive and Negative Affect Schedule (PANAS) [16] together with interviews and video recordings to evaluate visitor experiences of two interactive art installations. Similarly, Kortbek & Grønbaek [17] use a mixed methods approach including their own multiple-choice questionnaire and interviews to evaluate interactive installations in an art museum.…”
Section: Discussionmentioning
confidence: 99%
“…During this final selection round, consensus (i.e., a total score of 6, or 2 from each researcher) was needed for the articles to be included in data extraction. Ultimately, 13 articles were included (Bialoskorski et al, 2010;Costello et al, 2005;Deray and Simoff, 2012;Gurion and Jacoby, 2013;Her and Hamlyn, 2010;Hespanhol and Tomitsch, 2014;Hohl, 2009;Jacucci et al, 2009;Morgan and Gunes, 2013;Morrison et al, 2011bMorrison et al, , 2008Morrison et al, , 2011aMuller, 2008).…”
Section: Selection Processmentioning
confidence: 99%
“…They identified frameworks that discuss artwork characteristics, user interactions with them, or both. Similarly, Jacucci et al (2009) listed frameworks for studying aesthetic experiences with interactive art. However, none of these studies or the frameworks identified in them report actual participant responses.…”
Section: Introductionmentioning
confidence: 99%
“…In Coutrix et al [3], visitors' interactions with a virtual puppet on a public screen were analysed, detailing performative resources and recurring dramatic structure of sessions. Similarly, phases of collaborative explorations of a multimodal art installation were analysed in Jacucci et al [10]. These types of analysis are also applicable to non-artistic contexts such as interaction on a public display or collocated interaction with augmented reality [11,15].…”
Section: Performative Interaction In Hcimentioning
confidence: 99%